Antimicrobial activities of actinomycete isolates from rhizospheric soils in different mangrove forests of Torosiaje, Gorontalo, Indonesia - YULIANA RETNOWATI; SUKARTI MOELJOPAWIRO; TJUT SUGANDAWATY DJOHAN; ENDANG SUTARININGSIH SOETARTO (Society for Indonesian Biodiversity, 2018)
Retnowati Y, Moeljopawiro S, Djohan TjS, Soetarto ES. 2018. Antimicrobial activities of actinomycetes isolates from rhizospheric soil on different mangrove forests of Torosiaje, Gorontalo, Indonesia. Biodiversitas 19: 2196-2203. Mangrove forests are very productive ecosystems that form unique saline environment very rich in organic matter, containing nitrogen and sulfur available for microorganisms. Mangrove forest as an extreme environment is promising to be sources of antibiotic-producing actinomycetes. The objectives of this study were to analyze the antimicrobial activities of metabolites produced by actinomycete isolates from rhizospheric soil of mangrove forest of Torosiaje, Gorontalo, Indonesia, and identify the active compound for novel antibiotics production. Six isolates from a coastal mangrove forest was selected to produce secondary metabolite. The crude extract of the six selected actinomycete isolates showed antimicrobial activities against pathogenic microbes; the highest antimicrobial activities was indicated by metabolite produced by FUAm2-h1 and FMBg2-x3 isolates. The metabolite crude extracts produced by two potential isolates inhibited growth of pathogenic microbe on MIC value of 0.0625 to 0.5mgmL-1. Bio-autography assay detected an active compound on Rf value of 0.94, especially on extracellular metabolite produced by strain FUAm2-h1. The bioactive compounds were identified by liquid chromatography joined with low-resolution mass spectroscopy (LC/MS) and analysed by MEDINA's database The active compounds composed of 17 substances, and only 3 substances showed a high quantity with molecular weight of 507.37, 344.32 and 563.66 mol G-1, respectively. FTIR analyses identified the functional groups in the active compounds consisted of amide, amine, alkuna, alkane, NO2 nitro compound, alcohol, ether, carboxylic acid, ester and C-H aromatic ring. The biosynthesis of antibiotic on FUAm2-h1 and FMBg2-x3 isolates was regulated by double genes, i.e., PKS-II and NRPS genes. The antimicrobial activities of two actinomycete isolates showed the performance of antibiotics suspected as aromatics polyketides group. The FUAm2-h1 and FMBg2-x3 isolates showed high similarity with Streptomyces qinglanensis strain 172205 and Streptomyces sanyensis strain 219820, respectively, in terms of 16S rRNA gene sequences. The potential of those selected actinomycetes from extreme environments of mangrove forest constitute a source of promising actinomycete strains producing biologically active secondary metabolites.